¿Por qué a la didáctica, la epistemología, la informática y a las habilidades matemáticas, les cuesta tanto ingresar a una clase de Matemática? - Oteiza, Fidel (2019)
The approach to teaching is the heart of Mathematical Education and a preferred task of educators and researchers around the world. Epistemology is knowledge about the nature of mathematical knowledge. Digital technologies are the substance with which the symbolic space in which our students live and will live today is built. Mathematical skills are the focus of the curricular reforms of the discipline in recent decades. The school, and in it the Mathematics classroom, resists. Teaching prevails over learning. Adult presentations are more common than students doing Mathematics. There is an emphasis on content and algorithms over the abilities needed for mathematical work. Here we look for the assumptions and beliefs that could serve as a basis for the discrepancy between what is expected to happen in the Mathematics classroom and what is actually observed in it. The analysis seeks to understand what are the forces that hinder or inhibit the necessary evolution of the school and the school system.